2004
DOI: 10.2144/04366rr04
|View full text |Cite
|
Sign up to set email alerts
|

Tissue ischemia time affects gene and protein expression patterns within minutes following surgical tumor excision

Abstract: The aim of this study was to determine the impact of ischemia on gene and protein expression profiles of healthy and malignant colon tissue and, thus, on screening studies for identification of molecular targets and diagnostic molecular patterns. Healthy and malignant colon tissue were snap-frozen at various time points (3-30 min) after colon resection. Gene and protein expression were determined by microarray (HG-U133A chips) and surface-enhanced laser desorption/ionization time-of-flight mass spectrometry (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
3
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(148 citation statements)
references
References 29 publications
(19 reference statements)
10
134
3
1
Order By: Relevance
“…Although it is generally accepted that up to 2 hours of warm ischemia (time without fixation) does not alter protein, DNA or RNA conformation or preservation of microscopic, and IHC features (Burns et al 2009), Samaratunga et al (2011) have reported that even before resection has been completed, intraoperative manipulations can alter gene transcription levels during radical prostatectomies. Spruessel et al (2004) used microarray analysis, quantitative real-time polymerase chain reaction, and surface enhanced laser desorption ionization time of flight to investigate changes in gene and protein expression in normal and cancerous colon tissue at various stages of ischemia. Initial changes of gene and protein expression profiles were observed 5 minutes after resection; and after 30 minutes, 20% of all detectable genes and proteins differed significantly from baseline values.…”
Section: Specimen Collection and Transportationmentioning
confidence: 99%
“…Although it is generally accepted that up to 2 hours of warm ischemia (time without fixation) does not alter protein, DNA or RNA conformation or preservation of microscopic, and IHC features (Burns et al 2009), Samaratunga et al (2011) have reported that even before resection has been completed, intraoperative manipulations can alter gene transcription levels during radical prostatectomies. Spruessel et al (2004) used microarray analysis, quantitative real-time polymerase chain reaction, and surface enhanced laser desorption ionization time of flight to investigate changes in gene and protein expression in normal and cancerous colon tissue at various stages of ischemia. Initial changes of gene and protein expression profiles were observed 5 minutes after resection; and after 30 minutes, 20% of all detectable genes and proteins differed significantly from baseline values.…”
Section: Specimen Collection and Transportationmentioning
confidence: 99%
“…811,812 The possibilities of postmortem autolysis and fixation artifacts must always be taken into consideration when interpreting changes attributed to autophagy. 813 Analyses of these types of samples require not only special antigen retrieval techniques, but also histopathological experience to interpret autophagy studies by immunohistochemistry, immunofluorescence or TEM.…”
Section: 792mentioning
confidence: 99%
“…Limiting RNA degradation during tissue processing and quantifying RNA degradation by DF are important, particularly when clinical samples are used, because time intervals from sample procurement to RNA preservation impact RNA integrity (6 ). The use of RNA with comparable low DFs should provide microarray results that more accurately reflect biology rather than variable RNA degradation.…”
Section: Modification Of the Standard Trizolbased Technique Improves mentioning
confidence: 99%